CRITICAL REFORMS REQUIRED IN THE CURRICULUM OF ORAL BIOLOGY; A STUDENT FEEDBACK SURVEY - Sheikh, Qaiser Masud; Chaudary, Wajahat Ghafoor; Siddiqui, Saima; Jameel, Rafey Ahmad; Khan, Shah Salman; Farrukh, Umair (Pakistan Oral & Dental Journal, 2023)
The object was to revisit the conventional curriculum of the Oral Biology discipline, in light of the student’s feedback. This study was conducted at Foundation University College of Dentistry (FUCD), Islamabad. This is a qualitative explorative study, which comprised a period of 18 months in which the students were categorised according to their grades into two groups, the high achieving (70%-80%) and the low achieving (56%-62%), in the discipline of Oral Biology. Each group was introduced to two sessions of Focussed Group Discussion (FGD). The total students involved were 14. The reservations made by the students were grounded on six basic themes, which included: i) Teaching & learning styles, ii) Student’s concerns concerning 1st year BDS education, iii) Lack of collaborations amongst Teachers/Students, iv) Status of faculty teaching experience, v) Influence of student feedback in curriculum reforms and vi) Very less to non-existent interactive sessions in lectures. The above-mentioned 6 themes are the foundation for Oral Biology curricular reforms. This study noted some major reasons for the dropped scores of the students. Based on our results, some reforms were suggested and implemented in the curriculum of Oral Biology. The Medical Education Department offered workshops and teacher training courses to the faculty members helping them make their lectures more interactive and concept-building.